CHILDREN AND YOUNG PEOPLE'S SOCIAL MEDIA PLATFORMS BENEFITS AND IMPLICATIONS - Lela Susanty; Ardian Arifin; Darmadi Darmadi; Yuliana Yuliana; Ismawati Ismawati; Ahdi Topan Sofyan (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
This research aims to show the positive effects and the negative social media on the growth of young people. This discussion brings together the work of various fields of study the association between social media and social capital, personal safety of young people, psychological well-being, and learning performance. This research takes information from some of the posts that cover the same topic. Those selected are regular users of social media. The methodology used in this research is to use literature research with a theoretical framework developed for synthesis. The research shows that children and young people terbawa- bring positive social media to help improve their communication skills, get data, improve their technological expertise, as well as how they can use the latest technology efficiently. On the other hand, they are at risk of Facebook’s mental stress, cyberbullying, as well as online intimate harassment. The conclusion of this research is a social media platform is a very important role in the lives of young people every day. They find benefits by improving communication skills with friends and relatives and they can further improve their socialization process. Not only that, it can be said that young people can use social media to obtain data on topics such as health, education, as well as for improving the technical expertise using the latest technology.